Factors influencing the fixed deposit return in Perbadanan Hal-Ehwal Bekas Angkatan Tentera (PERHEBAT). Case study: Affin Bank Berhad / Nadiah Jamaluddin - Jamaluddin, Nadiah (Faculty of Business and Management, 2011)
This study was conducted to find out the significant of the factors influence the dependent variable with the independent variable. The variables selected are return gain in Fixed Deposits, interest rate by Affin Bank Berhad and the amount lend by Perhebat. The dependent variable is the return gains. The method used for this study is regression analysis. The result had interpret base on descriptive analysis, R squared analysis, hypotheses analysis (T-test), adjusted R squared and Durbin Watson. The data used were from the OBM system by Perhebat from years 2007 until 2010 with one month investment on selected month. Based from the result, the interest rate and the amount of lending have positive relationship toward the return gains by Perhebat.